Pelatihan Public Speaking Sebagai Strategi Pemberdayaan Pemuda dan Pemudi Desa Hutanamora dalam Menghadapi Tantangan Global - Ade Irma Simamora; Natalia Marjelita Purba; Febrian Tio Silaban (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Public speaking training serves as an effective step in enhancing the capacity of rural youth in facing the challenges of globalization and the Industrial Revolution 4.0 era. This study aims to empower the youth of Hutanamora Village through public speaking skills training as part of a community service program. The method applied uses a participatory approach involving 15 participants aged between 15 and 18 years. The results of the activity show a significant improvement in self-confidence, the ability to organize ideas, as well as verbal and nonverbal communication skills. In addition to technical improvements, the training also fostered critical awareness, reflective abilities, and stronger self-assurance when engaging with an audience. The implementation of this activity demonstrates that public speaking training is not only a practical learning tool but also a means of social empowerment and character development for the younger generation. Therefore, such training is recommended to be carried out continuously as part of youth development programs in rural areas.